Certain vs. uncertain actionable secondary findings in a cohort of 500 Lebanese participants: What to report to the patient? - Eileen Marie Hanna; Cybel Mehawej; Yazid Hoblos; Kelven Rahy; Andre Megarbane; Eliane Chouery (PLoS ONE, 2025)
Advances in next-generation sequencing enabled its integration into genetic diagnosis and have led to the uncovering of secondary findings. In this paper, we analyzed 500 Lebanese participants for pathogenic and likely-pathogenic variants in 81 recommended genes listed by the American College of Medical Genetics (ACMG). In this retrospective study, 500 individuals seeking genetic diagnosis through Exome Sequencing were included. Variants were analyzed and their pathogenicity assessed based on ACMG/AMP criteria and ClinVar. Secondary findings were identified in 16.8% of cases based on ACMG/AMP criteria, which decreased to 6% when relying on ClinVar. Dominant cardiovascular disease variants were predominant, constituting 6.6% based on ACMG/AMP assessments and 2% according to ClinVar. Additionally, using ACMG/AMP criteria, dominant oncogenic variants were identified in 4.2% of individuals, while recessive pathogenic variants were found in 4.8%. In contrast, ClinVar-based analysis reported these variants in 1% and 2.6% of the cohort, respectively. The high discordance between ACMG/AMP and ClinVar classifications (16.8% vs. 6%) underscores ethical dilemmas in deciding which criteria to prioritize for patient disclosure. Indeed, the absence of ACMG-classified pathogenic or likely pathogenic variants in ClinVar complicates reporting due to a lack of evidence linking them to disease in other individuals. Finally, the significant discrepancy between ACMG/AMP and ClinVar classifications emphasizes the urgent need to harmonize variant databases and update ClinVar entries, particularly for understudied populations such as the Lebanese cohort.